Fabrication methods and electrochemical study of various metallic nanoparticles (NPs) - De Jesus Cabrera, Edna (My University, 2024)
Metallic nanoparticles have size dependent properties that differ from those in bulk materials. Controlling the synthesis process is crucial to achieve various sizes and shapes. Depending on the size, metallic nanoparticles have properties that can be incorporated across several industries like pharmaceuticals, diagnostics, sensing, etc. Moreover, the electrochemical behaviour of an electrode may differ when different types of metallic nanoparticles are placed on its active surface. This thesis aims to synthesize various types of metallic nanoparticles, controlling their size, shape, and composition. Such as nanoparticles made of gold and expanding to gold core nanorods with metals like silver and platinum as shells. Then, the electrochemical behaviour of a glassy carbon electrode (GCE) would be studied by modifying the electrode with the final synthesis products. Synthesis of different shaped gold nanoparticles took place with non-seeding and seed-mediated growth methods. Capsule-shaped core@shell gold, silver, and platinum nanorods were synthesized with a non- seeding, colloid stabilizing and galvanic replacement method. The synthesized nanomaterials were characterized with UV-Vis spectroscopy and transmission electron microscopy (TEM). Followed by drop casting these various nanomaterials over a glassy carbon electrode (GCE) so that the electrochemical behaviour of the modified electrodes could be studied through cyclic voltammetry (CV) versus both PBS and Ru salt solutions. The characterization methods revealed different shapes, sizes, and compositions of metallic nanoparticles. Demonstrating how controlling the synthesis process can tailor the fabricated nanomaterials as desired. The electrochemical results showed that the glassy carbon electrode (GCE) behaviour changed when each of the synthesized nanoparticles were placed over its active surface. The findings in this thesis demonstrated the importance of controlling the synthesis of metallic nanoparticles and the impact they can have on the electrochemical behaviour of a glassy carbon electrode (GCE) when drop casted on their surface. This project has the potential to be expanded by investigating the impact of synthesized nanomaterials on the electrochemical behaviour of the electrode. Additionally, testing the modified electrode with various analytes containing biomolecules for exploring their potential applications in biosensing is a possibility.
Keywords: Nanoparticle, Core@shell, Electrode modification, Au@Pt nanoparticles, Nanorods